The role of Chlamydia pneumoniae, Mycoplasma pneumoniae in the development of infection in children with recurrent and chronic lung diseases - O.V. Kushelevskaya; T.B. Sentsova; I.K. Volkov ("Paediatrician" Publishers LLC, 2007)
And:O.N. Smirnova, S.A. Egorova Clinical manifestations of bleeding disorders in children of Stavropol Territory.A. Gromov, E.L. Semikina, L.S. Namazova Clinical and immunological value of the expression of membrane receptors in children with atopic asthma allergen during immunotherapyE.I. Ermolaeva The value of environmental and social factors in the development of peptic ulcer disease in adolescence